SPIRITUALITAS DIAKONIA GURU PENDIDIKAN AGAMA KATOLIK DALAM HIDUP MENGGEREJA DI PAROKI SANTA LUSIA PARLILITAN - Tarigan, Thomas Natalisa; Tibo, Paulinus; Hasugian, Sixgloria (Lembaga Penelitian STKIP Widya Yuwana, 2024)
Diaconal spirituality is the spirit of service in the church to carry out its mission. A Catholic religious education teacher must realize that he is called to carry out a mission of service that demands total sacrifice. Catholic religious education teachers are required to live up to the spirit of service by voluntarily providing knowledge, experience, skills, time, energy, thoughts and even all of themselves. Therefore, Catholic religious education teachers must be oriented towards fulfilling the needs of the people who concretely must show a distinctive spirituality with selfless self-sacrifice so that it is truly imbued with the spirituality of diaconal or service which is its specialty. This research was conducted to see how the diaconal spirituality of Catholic religious teachers at Santa Lucia Parlilitan Parish with the number of informants consisting of 7 people: catholic religious education teacher, head of the station council and parish priest. This study used qualitative research methods. Data collection techniques used in this study using observation techniques, interviews and documentation. This research was conducted from February to May 2023. The results showed that Catholic religion teachers had a diaconal spirituality by living up to ten virtues, namely: preparedness, totality, personal behavior, hard work and quality, sense of belonging, serving humbly, hope, fighting for truth, being grateful and hopeful which were applied to the five pillars of the church's duties, namely: liturgy, diaconal kerigma, martyria and koinonia.